2013
DOI: 10.1111/bdi.12041
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence for association between L‐type voltage‐gated calcium channel (CACNA1C) gene haplotypes and bipolar disorder in Latinos: a family‐based association study

Abstract: Objectives Through recent genome-wide association studies (GWAS), several groups have reported significant association between variants in the alpha 1C subunit of the L-type voltage-gated calcium channel (CACNA1C) and bipolar disorder (BP) in European and European-American cohorts. We performed a family-based association study to determine whether CACNA1C is associated with BP in the Latino population. Methods This study consisted of 913 individuals from 215 Latino pedigrees recruited from the United States,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
(57 reference statements)
0
16
0
1
Order By: Relevance
“…Furthermore, the KEGG pathway enrichment analysis (p<0.05) was performed for the 18 e "hotspots", define as at least two studies in several patients reported the cytogenetic locations were identified in epilepsy related phenotypes. 1A: 18 epilepsy-associated genes were significantly involved in a number of important biological pathways such as "Notch signaling pathway" and "Cell cycle" at P≤0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the KEGG pathway enrichment analysis (p<0.05) was performed for the 18 e "hotspots", define as at least two studies in several patients reported the cytogenetic locations were identified in epilepsy related phenotypes. 1A: 18 epilepsy-associated genes were significantly involved in a number of important biological pathways such as "Notch signaling pathway" and "Cell cycle" at P≤0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic DNA was extracted from blood using standard methods, as in our previous study [18]. Whole exome sequencing was performed at the next generation sequencing (deep sequencing), Illumina MiSeq at the Genome Core Facility at TTUHSC at El Paso.…”
Section: Whole Exome Sequencingmentioning
confidence: 99%
“…Collectively, these studies provide the strongest evidence to date for a specific polymorphism associated with BD. Nonetheless, given the modest magnitude (odds ratio approximately 1.2) of the association between rs1006737 and BD, and given similar findings in recurrent Major Depressive Disorder and schizophrenia (SCZ) (Athanasiu et al, 2010;Casamassima et al, 2010b;Gonzalez et al, 2013;Green et al, 2010Green et al, , 2012Nyegaard et al, 2010;Williams et al, 2011), rs1006737 is likely associated with symptom clusters and/or intermediate phenotypes that are salient to BD rather than with BD as a monolithic construct. rs1006737 has been positively associated both with high depression scores among BD patients as well as with psychotic BD specifically (Lett et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…In 2008, two genome-wide association studies found significant associations between BD and a single nucleotide polymorphism (SNP) on the calcium channel, voltage dependent, L type, alpha 1C subunit gene (CACNA1C), rs1006737 Sklar et al, 2008). Since then, studies have replicated the association between CACNA1C rs1006737 (henceforth, rs1006737) and BD (Fiorentino et al, 2014;Gonzalez et al, 2013;Green et al, 2013;Zhang et al, 2013). Collectively, these studies provide the strongest evidence to date for a specific polymorphism associated with BD.…”
Section: Introductionmentioning
confidence: 99%
“…All study participants were diagnosed using Diagnostic and Statistical Manual of Mental Disorders (DSM)-IV criteria using a best-estimation consensus procedure as previously described. 7 Of the 929 individuals in this study, 466 were diagnosed with BPI and 16 were diagnosed with SABP.…”
mentioning
confidence: 93%